Simulating shifting ecological states in a restored, shallow lake with multiple single-model ensembles: Lake Arreskov, Denmark. (October 2022) - Andersen, Tobias Kuhlmann; Nielsen, Anders; Jeppesen, Erik; Bolding, Karsten; Johansson, Liselotte S.; Søndergaard, Martin; Trolle, Dennis
Abstract: We investigated the ability of the process-based, 1-dimensional hydrodynamic-ecosystem lake model GOTM-WET to reproduce the fluctuating dynamics and shifts between turbid and clear water states following restoration in temperate, shallow Lake Arreskov, Denmark. The lake model was calibrated on a comprehensive 12-year dataset with a multiple single-model ensemble approach to address model parameter and performance metric uncertainty. Compared to earlier modelling attempts on this lake, the GOTM-WET model, which enables simulation of water column hydrodynamics such as stratification events and two zooplankton groups, improved the simulation of the maximum chlorophyll a concentrations during cyanobacteria blooms and zooplankton dynamics. However, the timing of shifts between phytoplankton and submerged macrophytes dominance following fish removal was not well reproduced, although both states were simulated. We discuss potential improvements of the model to enhance the ability to simulate the effects of restoration on the food web and ecological states in this and similar lakes. Highlights: We tested the ability of a new lake model to simulate effects of restoration. The 1D GOTM-WET model was used and represented by multiple single-model ensembles. The model reproduced short-term stratification events and surface algae blooms. Timing of shifts in ecological states following fish removal was not captured well.